Superparamagnetic FeCo and FeNi nanocomposites dispersed in submicrometer-ized C spheres - Ibrahim, Emad Monier Mosaad; Kath, Matthias; Gendy, Ahmed A. el; Klingeler, Rüdiger (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
Magnetic spheres with average diameter 100 nm, consisting of FeCo and FeNi nanomagnets (with average diameters 5.9 ± 1 and 4.6 ± 0.3 nm, respectively) dispersed in spherical carbon colloid have been synthesized using the radio frequency plasma-enhanced chemical vapor deposition technique. The nanoparticles are tightly embedded in the C matrix and well protected from oxidation. Superparamagnetic features such as typical Langevin-like magnetization curves are observed for the nanocomposites. A comprehensive analysis of the presence of dipolar interactions has been carried out within the framework of the mean-field model. The size of the nanoparticles constituting the carbon-spheres is near to the optimal value where Néel losses are maximal and considerable Neel-type specific absorption rates are observed. The material may hence provide a new material-based approach to realize biocompatibly protected superparamagnetic beads for application in biological environments, in particular, for magnetic hyperthermia.
Gesehen am 19.11.2018